Experiences of violent victimization and unwanted sexual behaviours among gay, lesbian, bisexual and other sexual minority people, and the transgender population, in Canada, 2018 - Jaffray, Brianna (Juristat, 2020)
Five dimensions of gender-based violence are explored: unwanted sexual behaviour while in public, unwanted sexual behaviour online, unwanted sexual behaviour in the workplace, sexual assault, and physical assault. * According to the 2018 Survey of Safety in Public and Private Spaces (SSPPS), an estimated 1 million people in Canada are sexual minorities-that is, they reported their sexual orientation as gay, lesbian, bisexual or a sexual orientation that is not heterosexual-representing 4% of the population of Canada 15 years of age and older. * In addition, approximately 75,000 people, or 0.24% of the population of Canada aged 15 and older indicated on the SSPPS that their assigned sex at birth was different from their current gender, or that they were neither male nor female-in other words, that they are transgender. Research suggests that sexual minority (those who stated their sexual orientation as lesbian, gay, bisexual, pansexual, asexual, or otherwise not heterosexual) people experience violence at a greater prevalence than heterosexual people (Simpson 2018; Walters et al. 2013). While this analysis will focus on the impacts of sexual orientation and gender on experiences of victimization and unwanted sexual behaviours, it is important to recognize that there are many aspects of a person that can intersect-such as their sexual orientation, gender, race, or whether they have a disability-and impact their likelihood of experiencing victimization (Crenshaw 1994). Experiences of sexual minority Canadians According to the 2018 Survey of Safety in Public and Private Spaces (SSPPS), an estimated 1 million Canadians are sexual minorities-that is, they reported their sexual orientation as gay, lesbian, bisexual or a sexual orientation that is not heterosexual-representing 4% of the population of Canada 15 years of age and older.